Correlates of opiate misuse based on aberrant urine drug tests for patients on chronic opiate therapy in a safety-net, academic primary care clinic - Bakhai, MD, MPH, FACP, Smita; Thilagar, MD, Bright; Reynolds, PhD, Jessica L.; Leonard, PhD, Kenneth E. (Journal of Opioid Management, 2018)
Objective: Determine correlates of opiate misuse based on urine drug test (UDT) among patients on chronic opiate therapy (COT) for chronic noncancer pain. Design: A cross-sectional study. Setting: Urban, academic clinic. Participants: UDT performed in 206 patients on COT for at least 3 months duration within a one-year period. Patients were classified based on UDT results: (1) Appearance of Opiate Adherence: Positive UDT for prescribed opiate and negative for illicit drugs and nonprescribed control substances; (2) Opiate Misuse; Overt nonadherence: (a) Positive UDT for illicit drugs and/or nonprescribed controlled substances AND positive or negative for prescribed opiates (b) Overdose; (3) Possible opiate nonadherence: Negative for prescribed opiates and negative for illicit and nonprescribed controlled substances. Interventions: None. Main outcome measures: UDT results, patient demographics, medical history, healthcare adherence, and utilization measures. Results: Of the 206 records analyzed, 80 (38 percent) had appearance of opiate adherence, 91 (44 percent) had misuse, and 35 (17 percent) had possible opiate nonadherence. Analysis was performed comparing misuse and appearance of opiate adherence groups. In bivariate analyses, history of smoking (OR 3.90, 95% CI 1.69-9.03), substance use (OR 7.02, 95% CI 2.56-19.20), missed medical appointments (OR 2.85, 95% CI 1.44-5.63), and nonadherence to other medications correlated with misuse group (OR 18.86, 95% CI 8.73-40.74). In logistic regression, only substance use history (OR 4.32, 95% CI 1.27-14.64) and nonadherence with nonopiate medications (OR 13.22, 95% CI 5.81-30.10) correlated with misuse. Conclusions: Medication nonadherence and missed appointments for other chronic conditions were significant correlates of opiate misuse.